Improving sustainability in wood coating: testing lignin and cellulose nanocrystals as additives to commercial acrylic wood coatings for bio-building - Jusic J (Italian Society of Silviculture and Forest Ecology (SISEF), 2021)
Wood use in bio-building should be considered as one of the main pillars of sustainability. According to international standards, beech wood (Fagus sylvatica L.) is a rather less durable species as it is subject to degradation due to weathering, though it is abundantly available to a more intense use. Service life of beech products and wood products in general can be enhanced by different methods, such as heat treatments, but new chances are offered by coating technologies. However, to ensure protection from wood-destroying organisms, most commercial coatings include components that could harm human health, other organisms and the environment. Therefore, coating industry has to develop more eco-friendly solutions in order to decrease its impact on human health and environment. The objective of this article was to modify commercial acrylic varnish by adding cellulose nanocrystals (CNC) and lignin (LN) extracted from beech wood and investigate their effect on water sorption, additive dispersion in the coating matrix and coating resistance to bacterial attack. Contact angle, weight gain and colour difference were analysed and FT-IR mapping was applied. The performance of CNC was promising, as it enhanced water sorption of the modified coating. However, protection against bacterial attack was not satisfying. On the other hand, chemically unmodified lignin did not show positive effects as component in the coating formulation. Nevertheless, the currently limited usage of these two renewable and abundant resources urgently calls for their more efficient utilization, in order to create additional value with industry side-streams producing novel bio-based materials. Further experiments are needed in order to obtain better dispersion of the particles and higher resistance to bacterial attacks.